2017
DOI: 10.3390/v9110321
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Resolution Structure of the Oncolytic Parvovirus LuIII by Electron Microscopy and 3D Image Reconstruction

Abstract: LuIII, a protoparvovirus pathogenic to rodents, replicates in human mitotic cells, making it applicable for use to kill cancer cells. This virus group includes H-1 parvovirus (H-1PV) and minute virus of mice (MVM). However, LuIII displays enhanced oncolysis compared to H-1PV and MVM, a phenotype mapped to the major capsid viral protein 2 (VP2). This suggests that within LuIII VP2 are determinants for improved tumor lysis. To investigate this, the structure of the LuIII virus-like-particle was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…Minor peaks on the DSF curve might be the result of partial unfolding of the capsid or the disassociation of capsid subunits from the whole, either of which would expose hydrophobic residues and result in increased fluorescence. The structure of the M. spretus EVE capsids at a resolution of 3.89 Å confirmed that the capsid structure was very similar to those of other rodent and porcine parvoviruses, with some rearrangements of the variable surface loops, as is customarily seen when comparing these viruses (26,40). M. spretus capsids showed uptake patterns by murine cells that were similar to those of extant mouse parvoviruses, with capsids having a perinuclear localization 1 h after uptake (25) (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Minor peaks on the DSF curve might be the result of partial unfolding of the capsid or the disassociation of capsid subunits from the whole, either of which would expose hydrophobic residues and result in increased fluorescence. The structure of the M. spretus EVE capsids at a resolution of 3.89 Å confirmed that the capsid structure was very similar to those of other rodent and porcine parvoviruses, with some rearrangements of the variable surface loops, as is customarily seen when comparing these viruses (26,40). M. spretus capsids showed uptake patterns by murine cells that were similar to those of extant mouse parvoviruses, with capsids having a perinuclear localization 1 h after uptake (25) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…8B). There was a pocket within the dimple of the capsid, near the 2-fold axis, which was similar to the sialic acid binding sites identified for other parvoviruses (26)(27)(28)(29) (Fig. 8C).…”
Section: Figsupporting
confidence: 66%
“…For each BuV1, BuV2, and BuV3 genotype, the structures were determined to 2.84, 3.79, and 3.25 Å resolution, respectively, and the VP2 structure ordered from residues 33 to 568, 33 to 567, and 33 to 572, respectively. This range of ~540 ordered residues is consistent with those of crystal and/or cryo-reconstructed structures available for other parvoviruses, including members of the protoparvoviruses [ 16 , 17 , 18 , 19 , 20 , 21 ]. The VP structure conserves the β-barrel (βB–βI) and α-helix A observed for all parvovirus structures.…”
Section: Introductionsupporting
confidence: 83%
“…Default settings were used. For structural comparison, the VP2 structures of these viruses (PDB IDs: CPV, 2CAS; FPV, 1C8E; H-1PV, 4GBT; LuIII, 6B8Q; MVM, 1Z14; PPV, 1K3V) [ 16 , 17 , 18 , 19 , 20 , 21 ] were compared to the BuV1 VP2 structure by secondary structure matching (SSM) in the PDBeFOLD program [ 39 ]. Distance differences at regions of non-overlapping Cα positions, due to deletions and insertions, were measured as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Those distinct interactions determine the tissue tropism of the AAVs and the gene delivery vectors derived from them (52). Cell infection and the tissue tropisms of the minute virus of mice (MVM) and H1 viruses are in some cases determined by variation in the specific interactions of the capsids with the host sialic acids (53,54). Complex virus-receptor interactions also occur in many other systems.…”
mentioning
confidence: 99%